Cytokine Augmentation Reverses Transplant Recipient Neutrophil Dysfunction Against the Human Fungal Pathogen Candida albicans. (8th January 2021) - Barros, Nicolas; Alexander, Natalie; Viens, Adam; Timmer, Kyle; Atallah, Natalie; Knooihuizen, Sally A I; Hopke, Alex; Scherer, Allison; Dagher, Zeina; Irimia, Daniel; Mansour, Michael K
Abstract: Background: Solid organ transplant (SOT) and stem cell transplant (SCT) recipients are at increased risk of invasive fungal disease despite normal neutrophil counts. Here, we measure neutrophil anti- Candida activity. Methods: Twenty-one SOT and 19 SCT recipients were enrolled 2–4 months posttransplant and compared to 23 healthy control patients (HC). Neutrophils were coincubated with Candida albicans, and percentage killing and swarming responses were measured. Results: Neutrophils from transplant patients had decreased fungicidal capacity compared to HC (42%, 43%, and 72% for SCT, SOT, and HC, respectively; SCT vs HC: P < .0001; SOT vs HC: P < .0001; SOT vs SCT: P = .8), including diminished ability to control hyphal growth (HC vs SOT: 0.1455 vs 0.3894, P ≤ .001; HC vs SCT: 0.1455 vs 0.6295, P ≤ .0001, respectively). Serum from SCT, but not SOT, recipients, inhibited the ability of HC neutrophils to control C. albicans (37%, 45%, and 55% for SCT, SOT, and HC, respectively). Neutrophils' control of hyphal growth was partially restored with granulocyte colony-stimulating factor or granulocyte macrophage colony-stimulating factor. Conclusions: Despite normal circulating numbers, our data suggest that neutrophils from SOT and SCT recipients mount dysfunctional responses against C. albicans . Intrinsic neutrophil changes and extrinsic serum factors may be responsible for the dysfunction, which is partially reversed with cytokine augmentation. Abstract : Solid organ and stem cell transplant recipients are at increased risk of invasive fungal disease despite normal neutrophil counts. Here, we show that their neutrophils mount dysfunctional responses against Candida albicans, which can be partially reversed with cytokine augmentation.